Hand grip diversity and frequency during the use of Lower Palaeolithic stone cutting-tools. Issue 125 (December 2018) - Key, Alastair; Merritt, Stephen R.; Kivell, Tracy L.
Abstract: The suite of anatomical features contributing to the unique gripping capabilities of the modern human hand evolved alongside the proliferation of Lower Palaeolithic flaked tool technologies across the Old World. Experimental studies investigating their potential co-evolution suggest that the use of flakes, handaxes, and other stone tools is facilitated by manipulative capabilities consistent with the evolutionary trajectory of the hominin hand during this period. Grip analyses have provided important contributions to this understanding. To date, however, there has been no large-scale investigation of grip diversity during flaked stone-tool use, empirical comparative analyses of grip use frequencies, or examination of ergonomic relationships between grip choice and stone tool type and form. Here, we conduct four experimental studies, using replica Lower Palaeolithic stone tools in a series of actualistic and laboratory-based contexts, to record grip type and frequency of grip use during 1067 stone tool-use events by 123 individuals. Using detailed morphometric data recorded from each tool, we demonstrate how grip choice varies according to the type and form of stone tool used, and how these relationships differ between tool-use contexts. We identify 29 grip types across all tool-use events, with significant differences recorded in their frequency of use dependent on tool type, tool form, and the context of use. Despite the influence of these three factors, there is consistency in the frequent use of a limited number (≤4) of grip types within each experiment and the consistent and seemingly forceful recruitment of the thumb and index finger. Accordingly, we argue that there are deep-rooted, ergonomically-related, regularities in how stone tools are gripped during their use, that these regularities may have been present during the use of stone tools by Plio-Pleistocene hominins, and any subsequent selective pressures would likely have been focused on the first and second digit.